2009
DOI: 10.1007/s00406-009-0038-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of disulfiram for alcohol-dependent patients and duration of outpatient treatment

Abstract: Despite the fact that alcoholism is a severe public health problem of worldwide proportions, only a limited number of medications is used as coadjuvant treatment. The objectives of this study were to analyse the use of disulfiram for alcohol-dependent patients and the immediate interruption of treatment following medication prescription. This is a transversal study of 810 patients who attended the Alcohol and Drug Research Unit (UNIAD) during the 2000-2006 period. The study showed that both male and female pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
4
0
3
Order By: Relevance
“…Analisando o tipo de estudo, sete artigos descrevem ensaios clí-nicos [5][6][7][8][9][10][11] , um trata-se de um relato de caso 12 e o artigo restante é uma revisão bibliográfica 13 . A realização de busca equivalente na base LILACS não resultou na identificação de outros artigos com estudos semelhantes que pudessem ser incluídos nesta lista.…”
Section: Resultados E Discussão Panorama Geral Das Publicações Brasilunclassified
See 2 more Smart Citations
“…Analisando o tipo de estudo, sete artigos descrevem ensaios clí-nicos [5][6][7][8][9][10][11] , um trata-se de um relato de caso 12 e o artigo restante é uma revisão bibliográfica 13 . A realização de busca equivalente na base LILACS não resultou na identificação de outros artigos com estudos semelhantes que pudessem ser incluídos nesta lista.…”
Section: Resultados E Discussão Panorama Geral Das Publicações Brasilunclassified
“…Destes, três conduziram ensaios clínicos (GREA 7,8,10,11 , UNIAD 5,6 e UFES 9 ). O quarto grupo (PROJAD) publicou um relato de caso 12 .…”
Section: Resultados E Discussão Panorama Geral Das Publicações Brasilunclassified
See 1 more Smart Citation
“…In addition, there is a great concentration of severely alcoholic patients and a rapid-acting medication is of great value provided that the patient understands the treatment goal, becomes motivated to keep abstinence, and has responsibility on the medication being taken. A recent study has proved that despite being an old drug, disulfiram is effective in keeping alcoholic individuals under outpatient treatment regardless of their gender 23 .…”
Section: Artigo Originalmentioning
confidence: 99%
“…In two trials, oral disulfiram was shown to reduce the frequency of drinking days, but it failed to improve relapse rates compared with placebo [24]. Patients using disulfiram tended to remain in treatment longer than those who did not use disulfiram or used a naltrexone-based treatment [25,26]. This finding is consistent with other studies showing that disulfiram, in particular, helped patients to maintain abstinence and to stay in treatment for longer periods [27].…”
Section: Introductionmentioning
confidence: 99%